Covid-19: A Pharmacotherapeutic Perspective - Khan, Bushra Hasan; Singh, Shivangna; Ahmad, Jameel; Ahmad, Farida (Asian Journal of Pharmaceutical Research and Development, 2021)
Introduction: COVID-19 disease has been difficult to tackle owing to the lack of typical therapeutic options. Many antivirals, antimalarial, and biologics are being carefully evaluated for treatment. This literature analysis aims to shed light to the ongoing studies concerning treatment possibilities for COVID-19 and assist as a reserve for health experts. Objectives: This literature review was done to underline the efficacy and safety of existing treatment alternatives for COVID-19 and the cautious use of non-steroidal anti-inflammatory drugs, angiotensin-converting enzyme inhibitors and angiotensin receptor blockers. Methods: PubMed, Medline, Embase and SCOPUS were meticulously browsed utilizing an amalgamation of the keywords "COVID 19," "SARS-CoV-2," and "treatment." All categories of articles together with clinical guidelines, case-studies and systematic reviews were assessed. Conclusions: Treatments that unswervingly target SARS-CoV-2 are not present so far; however, several antivirals (Remdesivir) and antimalarials (Hydroxychloroquine) have appeared as valuable treatment possibilities. Remdesivir and convalescent plasma may be expected to play a beneficial role in serious patients with respiratory failure. Interleukin-6 (IL-6) antagonists could also be utilized in patients who progress and display evidence of cytokine release syndrome. Corticosteroids need to be avoided lest there is a gripping indication for their usage. Available evidence for prevention and treatment of COVID-19 must be utilized till recognized treatments are derived into reality.